Quickly create a student account and their registration in courses OF MOODLE 2 PALATFORM - Scherbyna, О.А. (Journal of Information Technologies in Education (ITE), 2015)
When creating a platform for distance learning considerable efforts are required for formation and keeping up to date user accounts, as their numbers in higher education are measured in thousands. This work can be significantly sped up if the accounts do not create "from scratch",but import data on students from another database. Database established in the 2011 State Unified Electronic Database on Education (SUEDE) may serve this way, because of necessarily recorded data on all students in all higher educational institutions of Ukraine. Therefore, all of these schools may be interested in the proposed method of quick creation of student accounts in most popular in Ukraine distance learning platform Moodle by importing data exported from SUEDE and formed using a spreadsheet. This is supposed to create academic groups cohort, which allows teachers to record students on their courses as whole groups using still little known by us method of cohort synchronization, the features of usage of which is also discussed in this paper.